Stabilization of Laterite Soil with Eggshell Powder and Sodium Silicate used as fill Material in Road Construction - Oke, J. A.; Olowoyo, M. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The investigation carried out in this paper was to evaluate the effect of eggshell powder and sodium silicate as stabilizers to laterite soil used as fill material for the purpose of constructing light traffic pavement. The laterite soil used in this study was collected from Ikorodu North Local Government Area in Lagos State, Nigeria and treated with eggshell powder (ESP) and sodium silicate (SS) blend in stepped concentrations of 3% ESP + 2% SS, 6% ESP + 4% SS, 9% ESP + 6% SS, 12% ESP + 8% SS and 15% ESP + 10% SS by dry weight of the soil. Results from the tests carried out showed a general improvement on the engineering properties of the laterite treated with ESP and SS blend. Optimum California Bearing Ratio (CBR) tests results for un-soaked and soaked samples were recorded as 51% and 22% at 12% ESP + 8%SS content. Peak Unconfined Compressive Strength (UCS) values of 355 KN/m2 and 570 KN/m2 were recorded at 7- and 28-days curing periods respectively at an optimum blend of 12% ESP + 8%SS content. From the results obtained in this research, an optimum blend of 12% ESP and 8% SS using the West African Standard (WAS) compactive effort can be used to stabilize laterite soil material for use as fill material for the construction of light traffic roads. An advantage of applying the ESP is the decrease in the deleterious environmental impact of eggshell waste.